2011
DOI: 10.1111/j.1551-2916.2011.04939.x
|View full text |Cite
|
Sign up to set email alerts
|

Shape Distortion and Delamination During Constrained Sintering of Ceramic Stripes: Discrete Element Simulations and Experiments

Abstract: Particle‐based simulations using the discrete element method are applied for the sintering of thin ceramic stripes that are constrained by a rigid substrate. The inhibition of lateral particle movement in vicinity of the substrate leads to a preferred shrinkage direction perpendicular to the substrate, which causes shape distortion as well as delamination of the stripe at the interface edges. Multiple processing parameters are varied in simulations to analyze their influence on the mentioned effects. The amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Continuum theory of sintering, in its current state, is not able to account for these losses of continuity. The continuum theory of sintering could be combined with damage models or meso‐scale models in order to describe the development of these micro‐cracks and the consequent reduction of stresses. It is beyond the scope of this work to pursue such enrichments of the continuum theory of sintering.…”
Section: Resultsmentioning
confidence: 99%
“…Continuum theory of sintering, in its current state, is not able to account for these losses of continuity. The continuum theory of sintering could be combined with damage models or meso‐scale models in order to describe the development of these micro‐cracks and the consequent reduction of stresses. It is beyond the scope of this work to pursue such enrichments of the continuum theory of sintering.…”
Section: Resultsmentioning
confidence: 99%
“…35,36 Since the sintering simulations are used only for qualitative investigations the model parameters for the powders had not been determined in detail. Instead, existing data of an alumina powder have been used 36 and the systems were scaled to conform to the properties of the aforementioned study.…”
Section: Simulation Of the Sintering Processmentioning
confidence: 99%
“…For example, Henrich et al [12] found that crack initiation in the constrained film is related to particle rearrangement: if rearrangement is suppressed, cracks tend to form more easily because of increased local stresses. Rasp et al [13] found that particle rearrangement also affects the delamination of ceramic strips: an easier particle rearrangement inhibiting delamination at the edges of the ceramic strips. The work of Martin et al [10,14] led to the conclusion that, although geometrical constraint is necessary for a defect to grow into a crack, the presence of an initial defect is not a necessary condition to initiate cracks.…”
Section: Introductionmentioning
confidence: 99%
“…However the continuum mechanic analysis has difficulty in explaining how crack initiates. In recent years, some progress has been made in the fundamental understanding of crack initiation by using discrete element modelling (DEM) [10][11][12][13]. For example, Henrich et al [12] found that crack initiation in the constrained film is related to particle rearrangement: if rearrangement is suppressed, cracks tend to form more easily because of increased local stresses.…”
Section: Introductionmentioning
confidence: 99%